Vinegar residue biochar: A possible conditioner for the safe remediation of alkaline Pb-contaminated soil. (April 2022) - Li, Yuxin; Pei, Guangpeng; Zhu, Yuen; Liu, Wei; Li, Hua
Abstract: A better understanding how to modulate alkaline soil-plant systems with lead (Pb) toxicity with by vinegar residue biochar is important for the remediation of Pb-contaminated soil. Leaching column and pot experiments were conducted to investigate the effect of vinegar residue biochar on Pb speciation, soil properties, and plant growth under Pb stress. The results indicate that biochar could effectively decrease the exchangeable and carbonated-bound Pb but increase the Fe–Mn oxide and residue fractions in the soil with Pb at 500 mg kg −1 . Biochar did not effectively immobilize Pb in the soil with Pb at 1000 mg kg −1 . After leaching, biochar evidently increased the organic carbon and dissolved organic carbon content of the soil, but slightly affected the pH, cation exchange capacity and carbonate content. The biochar addition at 0.5% had no significant effect on soil aggregates, and biochar at 2.0% and 5.0% significantly decreased soil aggregate stability. The dry weight and soluble protein content of pak choi ( Brassica chinensis L.) increased with biochar treatment. Lead assimilation by plants was inhibited by the decreased availability of Pb in biochar-treated soils. Soil enzymes activities also significantly increased, then facilitated biochemical reactions in the soil environment. The applied biochar has shown an important role in mitigating Pb toxicity by increasing the soil organic carbon, dissolved organic carbon content, enzyme activities, and plant growth. The low dose biochar (0.5–2.0%) are recommended as references for subsequent experiments, especially in alkaline loam soil. Graphical abstract: Image 1 Highlights: Biochar from vinegar residue as an effective material for alleviating Pb stress in alkaline loam soil. Biochar facilitated Pb transformation from mobile fractions to non-mobile fractions. The content of Pb as a key factor for regulating the remediation effect of Pb-contaminated soil. Biochar remediation of Pb-contaminated soil by increasing the OC, DOC, enzymes activity of soil, and the growth of plant.